Global Warming Induced Water-Cycle Changes and Industrial Production: A Scenario Analysis for the Upper Danube River Basin - Christoph Jeßberger; Maximilian Sindram; Markus Zimmer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2010)
Using the environmental decision support system DANUBIA, we analyze the effects ofclimate change on industry and compare the effectiveness of different adaptation strategies.The observed area covers Germany and Austria up to 2025. Since the main effects ofclimate change in this region are expected to be caused through changes in the watercycle,we place a special focus on the exemplary region of the upper Danube catchmentarea. Industry is the main regional user of water resources. Water is an essential productionfactor and is used in almost every production process of a manufactured good. We applyestimates of regional production functions, based on AFiD-panel micro-data for Germany,to calibrate regional industrial production and water usage within DANUBIA. Thus, weare able to simulate region-specific effects of climate change and the impact of socialscenarios using an unprecedented model of reciprocal influences of a huge network ofinterdisciplinary research areas. Simulation results show wide regional differences inproduction site reactions as well as between differing scenarios. Comparing scenarios ofmoderate and serious climate change, we are able to illustrate the severe environmentaleffects in some regions and to determine considerable economic effects on regionaleconomic growth.
Keywords: D24; Q01; Q25; Q52; Q53; 330; Environmental decision support system; climate change; water-cycle; river basin management; Klimaveränderung; Feuchtgebiet; Donau; Regionale Entwicklung; Wirtschaftliche Anpassung; Management-Informationssystem; Industrielle Produktion; Deutschland; Österreich